Three-dimensional printing-guided percutaneous transcatheter replacement in coarctation of the aorta: a retrospective study - Qing He; Chennian Xu; Chennian Xu; Chennian Xu; Yang Liu; Ping Jin; Mengen Zhai; Rui Qiao; Zhiyuan Tian; Bin Cui; Jian Yang (Frontiers in Cardiovascular Medicine)
BackgroundTo evaluate the feasibility, effectiveness and assistant effect of 3D printed aortic model in the treatment on congenital coarctation of the aorta (CoA) in adolescents and adults.MethodsFrom December 2018 to December 2023, a total of 10 patients with congenital coarctation of aorta underwent percutaneous balloon dilatation covered stent implantation in the department of cardiovascular surgery, Xijing Hospital. There were 6 males and 4 females whose average age was (27.68 ± 13.45) years. One case complicated with ventricular septal defect (VSD). The CT data of aorta were collected before operation, and the aorta was reconstructed by Mimics software and printed with 3D printing technology. The operation simulation was performed before operation to determine the best operation plan. The clinical data during hospitalization and follow-up were analyzed.ResultsAll the patients of CoA were successfully treated with percutaneous balloon dilatation covered stent implantation. The narrowest average diameter of CoA increased from (4.35 ± 2.61) mm before operation to (16.84 ± 1.99) mm immediately after operation (P < 0.05). The mean transconstrictive systolic pressure difference decreased from (81.29 ± 18.72) mmHg before operation to (15.52 ± 7.47) mmHg after operation (P < 0.05). The mean systolic blood pressure of the right upper limb decreased from (182.05 ± 38.99) mmHg preoperatively to (141.95 ± 32.11) mmHg postoperatively (P < 0.05). The mean systolic blood pressure of the lower limb increased from (121.52 ± 27.84) mmHg preoperatively to (131.81 ± 32.39) mmHg postoperatively (P < 0.05). Two patients with PDA and VSD underwent interventional occlusion at the same time without shunt. During the period of hospitalization and follow-up, there were significant cardiovascular complications.ConclusionsPercutaneous balloon dilatation covered stent implantation is effective in the treatment of adolescents and adults with CoA in the short and medium term, with fewer complications, and the long-term effect needs furthshdie1er study.